Dados abertos para promover cidades inteligentes : possibilidades para municípios de médio porte - Sousa, Cleybson Miranda (2023)
This research explores the importance of open data platforms in driving innovation and development in medium-sized smart cities. It delves into the fundamental concepts of smart cities, different implementation approaches, and the role of open data, while analyzing the barriers to its implementation. Furthermore, case studies conducted in Matogrosso municipalities are presented, including an examination of the innovation ecosystem and an evaluation of city maturity. The results encompass case summaries, barrier identification, ecosystem characterization, and a proposed methodology for implementing open data platforms in cities. This research contributes to advancing knowledge in the fields of smart cities and open data.